2019
DOI: 10.3390/nu11092023
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Aglycones Attenuate Cigarette Smoke-Induced Emphysema via Suppression of Neutrophilic Inflammation in a COPD Murine Model

Abstract: Chronic obstructive pulmonary disease (COPD), a lung disease caused by chronic exposure to cigarette smoke, increases the number of inflammatory cells such as macrophages and neutrophils and emphysema. Isoflavone is a polyphenolic compound that exists in soybeans. Daidzein and genistein, two types of isoflavones, have been reported to have anti-inflammatory effects in various organs. We hypothesized that the daidzein-rich soy isoflavone aglycones (DRIAs) attenuate cigarette smoke-induced emphysema in mice. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…The cigarette smoke-exposed mice showed less weight gain, increased inflammatory cell infiltration in BALF, and development of emphysema characterized by alveolar enlargement and greater destruction of alveoli, similar to mice in a previous report. 23,33,34 Our results showed a discrepancy regarding the effect of NYT on smokinginduced change in pulmonary morphology: NYT induced partial recovery of alveolar damage as indicated by the DI; however, NYT did not reduce air space enlargement as indicated by the MLI. Some reports showed that the DI is a more sensitive parameter of pulmonary destruction than the MLI, 30,35 whereas others revealed a correlation between the MLI and loss of elastic recoil.…”
Section: Discussioncontrasting
confidence: 61%
“…The cigarette smoke-exposed mice showed less weight gain, increased inflammatory cell infiltration in BALF, and development of emphysema characterized by alveolar enlargement and greater destruction of alveoli, similar to mice in a previous report. 23,33,34 Our results showed a discrepancy regarding the effect of NYT on smokinginduced change in pulmonary morphology: NYT induced partial recovery of alveolar damage as indicated by the DI; however, NYT did not reduce air space enlargement as indicated by the MLI. Some reports showed that the DI is a more sensitive parameter of pulmonary destruction than the MLI, 30,35 whereas others revealed a correlation between the MLI and loss of elastic recoil.…”
Section: Discussioncontrasting
confidence: 61%
“…The level of alveolarization was determined by measuring the mean linear intercept (MLI). The mean interalveolar distance was measured as the MLI, by dividing the total length of lines drawn across the lung section by the number of intercepts encountered, as described [24]. For immunofluorescence, lung sections were then incubated at 4°C overnight with primary antibodies including mouse anti-surfactant protein C (SP-C, Abcam), mouse anti-von Willebrand factor (vWF, Cell signaling), and human anti-β2-microglobulin (β2MG, Santa Cruz Biotechnology, Dallas, TX, USA), which were visualized using FITC or Cy3-labeled secondary antibody (Jackson ImmunoResearch Europe Ltd., Newmarket, UK).…”
Section: Cell Adhesionmentioning
confidence: 99%
“…It is rich in important nutritional components, such as carbohydrates, vitamins, minerals, saponins, isoflavones, flavonoids, and peptides [ 28 ]. In particular, soy isoflavones are estrogenic polyphenols found in soybeans, and they have been reported to have anti-inflammatory effects [ 29 , 30 , 31 ]. An association between soy consumption and allergic diseases has been suggested [ 9 , 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%